Impact of agricultural land use on physicochemical properties of soils derived from sedimentary rocks in Malaysia - Wong, Mum Keng; Selliah, Paramananthan; Ng, Tham Fatt; Hassan, Meor Hakif Amir; Van Ranst, Eric; Inubushi, Kazuyuki (Taylor & Francis, 2020)
In Malaysia, soils derived from sedimentary rocks are extensively used for agricultural purposes with oil palm and rubber being the main dwellers. In order to understand the environmental impact of these perennial crops planting, the variability of physicochemical properties of 25 representative soils derived from sedimentary rocks under different ecosystems (agriculture land and natural forest) at six study sites spread across Malaysia was examined. Among the soil physicochemical properties, total soil organic carbon, total nitrogen, and fertility level were found to be generally higher in the forest ecosystems followed by rubber plantation and finally oil palm plantations. Likewise, projection of principal component analysis showed an associative relationship between soil physicochemical properties and microhabitats. Finally, this study showed that soils from different agricultural and natural sites, but derived from similar sedimentary rocks, had distinctive weathering conditions and soil properties. Therefore, site-specific field management according to soil type, soil management techniques as well as fertilizer strategies are required to maximize crop production and to sustain ecosystem services. The output of this study will enable farmers to improve their crop yield via the selection of suitable crops cultivation based on soil characteristics. © 2019, © 2019 Japanese Society of Soil Science and Plant Nutrition.